Conformational Domain Wall Switch. (11th March 2019) - Sharma, Pankaj; Sando, Daniel; Zhang, Qi; Cheng, Xiaoxing; Prosandeev, Sergey; Bulanadi, Ralph; Prokhorenko, Sergei; Bellaiche, Laurent; Chen, Long‐Qing; Nagarajan, Valanoor; Seidel, Jan
Abstract: Domain walls in ferroelectric materials have tantalizing potential in disruptive memory and reconfigurable nanoelectronics technologies. Here, a ferroelectric domain wall switch with three distinct addressable resistance states is demonstrated. The device operation hinges on fully controllable and reversible conformational changes of the domain wall. As validated by atomistic simulations consistent with the experiments, using electric field, the shape—and hence the charge state—of the domain wall and ultimately its conduction are altered. Sequential nanoscale transitions of the walls are visualized directly using stroboscopic‐piezoresponse force microscopy and Kelvin probe microscopy. Anisotropic head‐to‐head domain wall injection, stabilized by the majority carrier type of the ferroelectric, BiFeO3, is identified as the key factor that enables conformational control. Abstract : A conformational tristate ferroelectric domain wall switch is demonstrated with i) external field‐controlled selective regulation of the charge state of the ferroelectric domain wall interconnect and the associated large tunability of resistance, allowing for three distinct addressable states in the device and ii) nonvolatility and nondestructive readout of the stored information along with low‐energy operation.